Interpreting the Paramagnetic NMR Spectra of Potential Ru(III) Metallodrugs: Synergy between Experiment and Relativistic DFT Calculations - Novotný, Jan; Sojka, Martin; Komorovsky, Stanislav; Nečas, Marek; Marek, Radek (Journal of the American Chemical Society, 2016)
Ruthenium-based compounds are potential candidates for use as anticancer metallodrugs. The central ruthenium atom can be in the oxidation state +2 (e.g., RAPTA, RAED) or +3 (e.g., NAMI, KP). In this study we focus on paramagnetic NAMI analogs of a general structure [4-R-pyH](+)trans-[Ru(III)Cl4(DMSO)(4-R-py)](-), where 4-R-py stands for a 4-substituted pyridine. As paramagnetic systems are generally considered difficult to characterize in detail by NMR spectroscopy, we performed a systematic structural and methodological NMR study of complexes containing variously substituted pyridines. The effect of the paramagnetic nature of these complexes on the (1)H and (13)C NMR chemical shifts was systematically investigated by temperature-dependent NMR experiments and density-functional theory (DFT) calculations. To understand the electronic factors influencing the orbital (δ(orb), temperature-independent) and paramagnetic (δ(para), temperature-dependent) contributions to the total NMR chemical shifts, a relativistic two-component DFT approach was used. The paramagnetic contributions to the (13)C NMR chemical shifts are correlated with the distribution of spin density in the ligand moiety and the (13)C isotropic hyperfine coupling constants, Aiso((13)C), for the individual carbon atoms. To analyze the mechanism of spin distribution in the ligand, the contributions of molecular spin-orbitals (MSOs) to the hyperfine coupling constants and the spatial distribution of the z-component of the spin density in the MSOs calculated at the relativistic four-component DFT level are discussed and rationalized. The significant effects of the substituent and the solvent on δ(para), particularly the contact contribution, are demonstrated. This work should contribute to further understanding of the link between the electronic structure and the NMR chemical shifts in open-shell systems, including the ruthenium-based metallodrugs investigated in this account.